2006
DOI: 10.1086/509619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunologic Risk Factors for Meningococcal C Conjugate Vaccine Failure in the United Kingdom

Abstract: The antibody response in the subjects with vaccine failure was consistent with an anamnestic response, suggesting that MenC disease occurred despite the MCC vaccine priming for immune memory. Persistence of antibodies may be a more appropriate correlate of long-term protection for MCC vaccines than the ability to generate a booster response on exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 27 publications
5
72
0
4
Order By: Relevance
“…1 In the United Kingdom, individuals who received meningococcal serogroup C conjugate but who also developed invasive disease despite strong evidence of immune memory, had low serum bactericidal antibody titers. 2 Similar findings have been observed among Hib vaccine failures, 3 a circumstance that highlights the importance of persistence of immune responses after vaccination. Complement-mediated bacteriolysis of meningococci, measured by serum bactericidal assay is the established correlate of protection against invasive meningococcal disease.…”
Section: Introductionsupporting
confidence: 62%
“…1 In the United Kingdom, individuals who received meningococcal serogroup C conjugate but who also developed invasive disease despite strong evidence of immune memory, had low serum bactericidal antibody titers. 2 Similar findings have been observed among Hib vaccine failures, 3 a circumstance that highlights the importance of persistence of immune responses after vaccination. Complement-mediated bacteriolysis of meningococci, measured by serum bactericidal assay is the established correlate of protection against invasive meningococcal disease.…”
Section: Introductionsupporting
confidence: 62%
“…Finally, in the work by Goldschneider et al, 24,25 a titer of 4 with intrinsic human complement correlated with and was established as the threshold of clinical protection, while a more conservative threshold of 8 was selected as a clinical endpoint for licensure of MenACWY conjugate vaccines. Our data, and those generated for other licensed meningococcal vaccines, demonstrate that the increase of the threshold has had very limited impact on the assessment of immunogenicity at 1 month after primary vaccination.…”
Section: Limitationsmentioning
confidence: 99%
“…The primary measures of immunogenicity were the percentages of subjects who achieved hSBA titers 8, and the hSBA geometric mean titers (GMTs), against serogroups A, C, W, and Y reference strains. Although Goldschneider et al demonstrated that an hSBA titer of 4 was the threshold for clinical protection, 24,25 a more conservative threshold of 8 was used for assessment of MenACWY-CRM vaccine-induced immunogenicity in support of vaccine licensure. The same threshold was also used for characterization of bactericidal antibody persistence.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of immunological memory has been demonstrated in some cases of Hib and MenC vaccine failures (significantly higher convalescent Ab titres were found in cases than in vaccine-naive controls) (14,15). Furthermore, Ab kinetic studies in primed adolescents showed that it takes 5 d to increase serum functional Ab following MenC polysaccharide antigenic challenge (16).…”
mentioning
confidence: 99%